La adaptación y su incidencia en la socialización de los niños y las niñas del primer año de educación básica de la escuela “Luis Alfredo Samaniego Arteaga” del cantón Catamayo provincia de Loja período 2011-2012 - Mejía Hidalgo, Nancy Adriana (2014)
This research work the adaptation and socialization Concerns IMPACT ON CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL "LUIS ALFREDO SAMANIEGO ARTEAGA" Loja province CATAMAYO CANTON 2011-2012. THEREFORE we propose Overall objective: To inform parents and teachers about the Importance of adaptation and its Influence in the socialization of children and girls. The family is the first person With The social relation, primary socialization agent is the first source of information for the child know about Their worth, the rules of the roles and expectations That Are Projected onto family meets him. The different functions Such as Providing Financial and Emotional Stability, if the child is well at home will allow you to socialize Gradually, Adapting to different contexts as part of Establishing relationships With Others, Develop behaviors based on the Norms, Values and Principles That Govern society . Simultaneously this dimension Involves the construction of personal identity, self-concept and self-esteem in a World in Which You Set affective ties, express emotions, Develop empathy and helping behaviors. All this contributes to the achievement of well-being and personal balance. Given the important Contributions In This area of development of the child, the educator must know the evolutionary characteristics, to Stimulate Their development and minimize the potential Difficulties That Could Arise in the process of adaptation. For the realization of this topic as some methods used are: scientific, inductive, analytical and statistical, as well as techniques and tools used more relevant as the survey of teachers and parents and children to an observation sheet allowed us to Obtain the Necessary information, Malthus and know the level of adaptation and socialization with children entering the establishment, the school "Luis Samaniego Alfredo Arteaga". The integration of the child to the school is a process by Which We Will Strengthen the cognitive, motor areas, language area, and Especially the Social-Emotional Area. Parents must to prepare children for this process of transformation That each infant live help and guide, Should teachers, draw: projects, strategies, techniques, early childhood education in taking Responsibility for Facilitating the bond of affection, mutual trust, friendliness, safety, preparing to Facilitate the separation of the child and the family so the child stays in That school is significant. The population consisted of three teachers, seventy and seventy children family parents. And so awareness among parents That It Is Your Responsibility to Provide Stability for children girls emotional Easier integration to the first year of basic education: and With The help of teachers Affect this process UNLESS the child